Pengaruh Disiplin Kerja dan Kompensasi terhadap Kinerja Pegawai Pada Badan Keuangan Daerah Kabupaten Tanjung Jabung Timur - Said Almadudi (J-MAS (Jurnal Manajemen dan Sains), 2022)
This reseach was to analyse how the effect of dicipline and compensation on job performance . How to as well as a condition of dicipline, compensation and job performance at the Financial Agency Area of East Tanjung Jabung Regency..The research methodology is descriptive and quantitative analysis methods. Data used is secondary data.The population become object in this research is job performance at Financial Agency Area of East Tanjung Jabung Regency. The method for analysis is analysis multifly regression, hypotesis test, correlation so determinant coefficient and F_tes so t_test. The object of this research is employees at the Financial Agency Area of East Tanjung Jabung Regency. This office is a branch of Financial Agency Area of East Tanjung Jabung Regency. which is the task of collect tax on earth and buildings and other taxes in the east Tanjung Jabung area.Analysis on the research of respondents felt a high work discipline and good compensation in the performance of tasks provided by the superiors. In the statement of respondents the indicator comes and home work on time shows the highest score, which is a score of 252,5 verry high categories. Multiple linear regression equations are Y = 14.439 + 0.049X1 + 0.323X2 + e. Independent variables (discipline and compensation) simultaneously have significant effect on the dependent variables (performance employees). While partial only compensation affects performance employees and variable discipline not affects of the performance employees. Conclusion that the discipline and compensation simultaneously have significant effect on performance employees. Only compensation had effect to performance employees and have a positive relationship.